Long term outcomes of hepatic resection following orthotopic liver transplant. Issue 3 (19th December 2021) - Murphy, Skyle; Hodgkinson, Peter; O'Rourke, Thomas R.; Slater, Kellee; Yeung, Shinn; Fawcett, Jonathan
Abstract: Background: Liver resection is sometimes used as a graft saving procedure following orthotopic liver transplantation. Methods: In this single centre retrospective cohort study, 12 adult patients underwent resection over a 20 year period, including recipients of split livers and second grafts. Results: Indications for resection were vascular (portal vein obstruction and hepatic artery thrombus), biliary (ischaemic cholangiopathy, chronic biliary obstruction, biliary‐vascular fistula and biloma) and recurrence of disease (primary sclerosing cholangitis [PSC] and hepatocellular carcinoma [HCC]). There was no perioperative mortality. Median follow up was 89 months. At the completion of the study 40% of patients had functioning grafts. One third required retransplantation with a median 1 year 6 months post resection. Three patients were deceased (recurrent HCC n  = 1, PSC n  = 1 and unspecified causes n  = 1). Total graft survival was 91.7% at 1 year, 73.3% at 5 years and 64.2% at 10 years. Conclusions: Liver resection following liver transplant in select patients may salvage the graft or delay the need for retransplantation. Abstract : In this single centre retrospective cohort study, 12 adult patients underwent resection over a 20 year period, including recipients of split livers and second grafts. At the completion of the study 40% of patients had functioning grafts with total graft survival was 91.7% at 1 year, 73.3% at 5 years and 64.2% at 10 years. Liver resection following liver transplant in select patients may salvage the graft or delay the need for retransplantation.